Inhibition of EPAC1 signaling pathway alters atrial electrophysiology and prevents atrial fibrillation - Guillot, Bastien; Boileve, Arthur; Walton, Richard; Harfoush, Alexandre; Conte, Caroline; Sainte-Marie, Yannis; Charron, Sabine; Bernus, Olivier; Recalde, Alice; Sallé, Laurent; Brette, Fabien; Lezoualc’h, Frank (Frontiers in Physiology, 2023)
Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and is associated with increased mortality and morbidity. The Exchange Protein directly Activated by cAMP (EPAC), has been implicated in pro-arrhythmic signaling pathways in the atria, but the underlying mechanisms remain unknown. In this study, we investigated the involvement of EPAC1 and EPAC2 isoforms in the genesis of AF in wild type (WT) mice and knockout (KO) mice for EPAC1 or EPAC2. We also employed EPAC pharmacological modulators to selectively activate EPAC proteins (8-CPT-AM; 10 μM), or inhibit either EPAC1 (AM-001; 20 μM) or EPAC2 (ESI-05; 25 μM). Transesophageal stimulation was used to characterize the induction of AF in vivo in mice. Optical mapping experiments were performed on isolated mouse atria and cellular electrophysiology was examined by whole-cell patch-clamp technique. In wild type mice, we found 8-CPT-AM slightly increased AF susceptibility and that this was blocked by the EPAC1 inhibitor AM-001 but not the EPAC2 inhibitor ESI-05. Consistent with this, in EPAC1 KO mice, occurrence of AF was observed in 3/12 (vs 4/10 WT littermates) and 4/10 in EPAC2 KO (vs 5/10 WT littermates). In wild type animals, optical mapping experiments revealed that 8-CPT-AM perfusion increased action potential duration even in the presence of AM-001 or ESI-05. Interestingly, 8-CPT-AM perfusion decreased conduction velocity, an effect blunted by AM-001 but not ESI-05. Patch-clamp experiments demonstrated action potential prolongation after 8-CPT-AM perfusion in both wild type and EPAC1 KO mice and this effect was partially prevented by AM-001 in WT. Together, these results indicate that EPAC1 and EPAC2 signaling pathways differentially alter atrial electrophysiology but only the EPAC1 isoform is involved in the genesis of AF. Selective blockade of EPAC1 with AM-001 prevents AF in mice.